Carbon footprint of yerba mate (Ilex paraguariensis) value chain in Misiones Province (Argentina) - Chifarelli, Diego Hernan; Gruber, Lorena; Azzini, Lapo; Nicese, Francesco Paolo; Giordani, Edgardo (MDPI, 2025)
Yerba mate (YM) is an important crop derived from the cultivation of the native tree Ilex paraguariensis in northeastern Argentina, used for the preparation of mate infusion, which is widely consumed in South America. This study aimed at assessing the environmental impact, namely of CO2 equivalent (CO2eq.) emissions, of the YM value chain while identifying environmental hotspots along the production chain, from nursery up to transport. A cradle-to-wholesale approach was carried out, considering as the main functional unit 1 kg of commercial YM produced in Misiones Province and transported to Buenos Aires, the largest YM market in the world. Primary data were gathered from representative nurseries and plantations of the region; processing and packaging data were collected from a local cooperative, while the assessment of the impact due to truck transport was performed considering a distance of 1200 km from Buenos Aires. All the processes were analyzed using LCA methodology following the guidelines outlined in the ISO 14044 regulation (EN ISO 14044); the GaBi software (Sphera Solution, Inc., Chicago, IL, USA), updated to version 10.7.21.8, was used for process modeling, while the CML 2001 calculation method, updated as of the latest release in August 2016, was used to calculate the impacts. The results (1.24 kg CO2eq./kg. YM produced in Misiones and transported to Buenos Aires) show that the cultivation phase of YM has very little impact, while most of the emissions are related to the drying phase and the subsequent transportation from the production area to Buenos Aires.